2017
DOI: 10.1016/j.jmps.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion, slide, and rupture of an elastomeric seal

Abstract: Abstract. Elastomeric seals are essential to two great technological advances in oilfields:horizontal drilling and hydraulic fracturing. This paper describes a method to study elastomeric seals by using the pressure-extrusion curve (i.e., the relation between the drop of pressure across a seal and the volume of extrusion of the elastomer). Emphasis is placed on a common mode of failure found in oilfields: leak caused by a crack across the length of a long seal. We obtain an analytical solution of large elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…They observed that in swellable elastomer packer equipment, contact stress profile peaks at the center of the element and declines towards both ends of the axial length. Wang et al [25] studied elastomer failure modes such as extrusion, sliding, and rupture by conducting theoretical analysis supported by visual experimental observations. Zhong et al [26] used FEA model of large bore expandable liner hanger to assess expansion force, cone pull out fore, contact stress at the seal-pipe interface, and deformations in hanger, casing, containment spikes, and cone body.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed that in swellable elastomer packer equipment, contact stress profile peaks at the center of the element and declines towards both ends of the axial length. Wang et al [25] studied elastomer failure modes such as extrusion, sliding, and rupture by conducting theoretical analysis supported by visual experimental observations. Zhong et al [26] used FEA model of large bore expandable liner hanger to assess expansion force, cone pull out fore, contact stress at the seal-pipe interface, and deformations in hanger, casing, containment spikes, and cone body.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[40] Improvement of hardness and compression set properties of EPDM seals with alternating multilayered structure [41] Method for the evaluation of elastomeric seals by compression stress relaxation [42] The influence of rubber material on sealing performance of packing element in compression packer [43] Stress relaxation in viscoelastic materials [44] Improvement of hardness and compression set properties of EPDM seals with alternating multilayered structure [41] Extrusion, slide, and rupture of an elastomeric seal [45]…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Sealing force prediction of elastomeric seal material for PEM fuel cell under temperature cycling [32] Stress relaxation behaviour of EPDM seals in polymer electrolyte membrane fuel cell environment [33] Sealing force prediction of elastomeric seal material for PEM fuel cell under temperature cycling [34] Temperature-dependent leak tightness of elastomer seals after partial and rapid release of compression [35] Long-term stress relaxation prediction for elastomers using the time-temperature superposition method [36] Improvement of hardness and compression set properties of EPDM seals with alternating multilayered structure [37] Method for the evaluation of elastomeric seals by compression stress relaxation [38] The influence of rubber material on sealing performance of packing element in compression packer [39] Stress relaxation in viscoelastic materials [40] Improvement of hardness and compression set properties of EPDM seals with alternating multilayered structure [37] Extrusion, slide, and rupture of an elastomeric seal [41]…”
Section: Titlementioning
confidence: 99%